Identification of sea grape (Caulerpa racemosa) content using X-Ray Fluorescence (XRF) spectrometer - Susilawati, Dewi; Fendi, Fendi; Rochmady, Rochmady; Rakhfid, Abdul; Mosriula, Mosriula (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
Seaweed possesses the potential to serve as a functional food or supplement, being nutrient-dense and a source of food and medicine due to its abundance of minerals, vitamins, and antioxidants. In Indonesia, seaweed is extensively utilized due to its advantageous properties for multiple industries, including agriculture, animal husbandry, pharmaceuticals, chemicals, and medicine. This study seeks to discover a specific component of sea grape (Caulerpa racemosa), which is prevalent in the waters of Lohia Village, Lohia District, Muna Regency, Southeast Sulawesi. The composition of sea grape (Caulerpa racemosa) was analyzed utilizing an X-ray Fluorescence Spectrometer (XRF) due to its capacity to detect nearly all minerals in a single measurement. The study's findings indicated that sea grapes (Caulerpa racemosa) at stations 1, 2, and 3 contained Chlorine (Cl), Calcium (Ca), Potassium (K), and Bromine (Br), along with several trace elements including Iron (Fe), Phosphorus (P), Strontium (Sr), Silicon (Si), and Titanium (Ti) in minor quantities. At stations 4, 5, and 6, sea grapes (Caulerpa racemosa) predominantly exhibited Chlorine (Cl), Potassium (K), and Magnesium (Mg), whereas Calcium (Ca) and Bromine (Br) were present in lesser quantities. Despite the considerable benefits of sea grapes (Caulerpa racemosa) for humans, caution is imperative in their use. Sea grapes (Caulerpa racemosa) possess the capacity to absorb minerals and bioaccumulate heavy metals from seawater, resulting in the presence of trace elements.